Reflections on professional abilities for working in the Nuclei of Support to Family Health - Dupas Gonçalves do Nascimento, Débora; de Campos Oliveira, Maria Amélia (O Mundo da Saúde, 2010)
The Nuclei of Support to Family Health (NASF), recently implanted in Brazil, aim at supporting family health teams in implementing the network of health services and broaden the public and the target of Basic Assistance actions. Its implantation reflects the increasing effort for integrality in assistance and interdisciplinarity of health actions, aiming at the consolidation of the Family Health Strategy. This article presents some reflections concerning the tools used in NASF daily activities and the required professional abilities. An inconsistence between initial training and the concrete reality of services was perceived which challenges us to answer to the social necessities in the health field. A training grounded in the four pillars of education proposed by Delors may contribute to educating professionals with knowledge, abilities and attitudes necessary for working in NASF.